If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -15 = 11x + -68 Reorder the terms: -15 + 2x = 11x + -68 Reorder the terms: -15 + 2x = -68 + 11x Solving -15 + 2x = -68 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -15 + 2x + -11x = -68 + 11x + -11x Combine like terms: 2x + -11x = -9x -15 + -9x = -68 + 11x + -11x Combine like terms: 11x + -11x = 0 -15 + -9x = -68 + 0 -15 + -9x = -68 Add '15' to each side of the equation. -15 + 15 + -9x = -68 + 15 Combine like terms: -15 + 15 = 0 0 + -9x = -68 + 15 -9x = -68 + 15 Combine like terms: -68 + 15 = -53 -9x = -53 Divide each side by '-9'. x = 5.888888889 Simplifying x = 5.888888889
| 60h-45h=-1200+1800 | | -5+14=16x-4-15x | | x*15+28=x*5+328 | | 5x=7/3 | | x*5+28=x*5+328 | | 49x^264=0 | | 16x^2+72xy+81y^2=0 | | 1.28v+1.77v+1.34=1.79 | | (1/240)+(1/x)=(1/144) | | 30x^2+38x+12=0 | | 3(7x-2)=22x | | (3+2n)/7=5 | | .3333333t-.66666666=3 | | 8b^2-9b+1= | | 4(2c-1)-3=4c+5 | | 2-c=20 | | 50x^2-60x+18=0 | | -9(t+6)=27 | | 4(4c-1)-6=12c+2 | | 12x^2-60x+75=0 | | (x-2)/8=0.75 | | 34-18=4(x-4) | | 4x^2-9x+6=0 | | x+21+4x=-22-4x-29 | | f(x)=7xsquared-4x | | 6b^2-11bw-35w^2= | | (3/2x+20)+2x=90 | | 6t^2-14t-12=0 | | (7.1+3.5)x=45.9+x | | -12n+12=-8n-4 | | 3log(x+2)=3.5 | | (1/28)+(1/21)=(1/x) |